Canada's Decentralized "Human-Driven" Approach During the Early COVID-19 Pandemic - Hansen, Gregory; Cyr, Amelie (JMIR Publications, 2020)
A country's early response to a pandemic is critical for controlling the disease outbreak. During the COVID-19 pandemic, a number of southeast Asian countries adopted centralized, coordinated, rapid, and comprehensive approaches that involved smart technology (the "techno-driven" approach). In comparison, Canada's approach appeared to be decentralized, uncoordinated, and slow, and it focused on educating citizens and enhancing social and human capital (the "human-driven" approach). We propose that in future pandemics, early and coordinated "techno-driven" approaches should receive more careful consideration to curtail outbreaks; however, these approaches must be balanced with protecting individuals' freedoms.